Development of in-situ monitoring systems for the thermoforming of pre-preg composite laminates - Land, Patrick; Branson, David T.; Crossley, Richard J.; Ratchev, Svetan (2016)
Recent developments in automated composite manufacturing technologies, such as Automated Fibre Placement, AFP, and Automated Tape Layup, ATL, have enabled larger components to be produced efficiently, leading to an increased use of prepreg composites in aerospace. These processes are limited in the geometry that may be produced and therefore secondary forming processes are commonly required for implementation. There is, therefore, a need to improve reliability and increase forming capability using these processes, whilst ensuring that defects in the laminate are limited. Thermoforming of composite and polymer materials is a well-known forming method for use with polymers and polymer based materials. This paper will discuss the monitoring methods and results used in a typical thermoforming process based on experimental results from a composite material during Thermal Roll Forming (TRF). The focus of this testing is to characterise the effect of temperature and dynamic contact forces on the composite against the real-time development of defects such as wrinkles during TRF forming.